RNA viruses in trypanosomatid parasites: a historical overview - Grybchuk, Danyil; Kostygov, Alexei Y; Macedo, Diego H; d'Avila-Levy, Claudia M; Yurchenko, Vyacheslav (Memorias do Instituto Oswaldo Cruz, 2018)
Viruses of trypanosomatids are now being extensively studied because of their diversity and the roles they play in flagellates' biology. Among the most prominent examples are leishmaniaviruses implicated in pathogenesis of Leishmania parasites. Here, we present a historical overview of this field, starting with early reports of virus-like particles on electron microphotographs, and culminating in detailed molecular descriptions of viruses obtained using modern next generation sequencing-based techniques. Because of their diversity, different life cycle strategies and host specificity, we believe that trypanosomatids are a fertile ground for further explorations to better understand viral evolution, routes of transitions, and molecular mechanisms of adaptation to different hosts.
Keywords: RNA-viry; Animals; Host Specificity; Microscopy, Electron, Transmission; transmisní elektronová mikroskopie; zvířata; Trypanosomatina; RNA Viruses; Leishmaniavirus; hostitelská specificita